Differentiate:

a. y = (x + 3)(x^2 −5x +1)

b. y = x^2e^x

Similar Questions
  1. 1. differentiate cos(3/x)2. differentiate sin(4/x) 3. differentiate 3/{sin(3x+pi)} 4. differentiate pxsin(q/x)where p and q are
    1. answers icon 0 answers
    1. answers icon 1 answer
  2. 1) solve:e^x(x^2-4)=0e^x=0 and then (x+2)(x-2) so x=2, -2 2) differentiate: y=ln(6x^2 - 3x + 1) 1/(6x^2 - 3x + 1) * 12x-3 3)
    1. answers icon 4 answers
  3. I'm having problems with this one. Can't get the right answer.Differentiate the following using the chain rule. f(x) =
    1. answers icon 1 answer
more similar questions